2021
DOI: 10.3389/fmicb.2021.616979
|View full text |Cite
|
Sign up to set email alerts
|

Review: Lessons Learned From Clinical Trials Using Antimicrobial Peptides (AMPs)

Abstract: Antimicrobial peptides (AMPs) or host defense peptides protect the host against various pathogens such as yeast, fungi, viruses and bacteria. AMPs also display immunomodulatory properties ranging from the modulation of inflammatory responses to the promotion of wound healing. More interestingly, AMPs cause cell disruption through non-specific interactions with the membrane surface of pathogens. This is most likely responsible for the low or limited emergence of bacterial resistance against many AMPs. Despite t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
192
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(260 citation statements)
references
References 199 publications
0
192
0
9
Order By: Relevance
“…It acts by induction of pore formation following interaction with membrane surfaces (van den Bogaart et al, 2008). Since it also shows anti-inflammatory properties (Lee and Bae, 2016), the Food and Drug Administration (FDA) approved its usage in clinical practice (Dijksteel et al, 2021), for relieving pain associated to tendinitis, arthritis, sclerosis multiple (Park et al, 2004;Son et al, 2007;Yang et al, 2011). Amphibians, especially frogs, are a rich source of AMPs.…”
Section: Animals As Source Of Ampsmentioning
confidence: 99%
See 2 more Smart Citations
“…It acts by induction of pore formation following interaction with membrane surfaces (van den Bogaart et al, 2008). Since it also shows anti-inflammatory properties (Lee and Bae, 2016), the Food and Drug Administration (FDA) approved its usage in clinical practice (Dijksteel et al, 2021), for relieving pain associated to tendinitis, arthritis, sclerosis multiple (Park et al, 2004;Son et al, 2007;Yang et al, 2011). Amphibians, especially frogs, are a rich source of AMPs.…”
Section: Animals As Source Of Ampsmentioning
confidence: 99%
“…However, many others, both natural and synthetic, are still under clinical trials ( Table 3 ). Preliminary results suggested that many AMPs could be useful alone or in synergy with common antibiotics to prevent or treat several diseases, but most of the studies are still ongoing or were stopped because of issues that can be solved, including unfavorable pharmacokinetic profile or unexpected side effects ( Browne et al., 2020 ; Dijksteel et al, 2021 ).…”
Section: Amps In Ongoing Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The AMPs, also known as host defense peptides (HDPs) are commonly found in multicellular eukaryotes, usually expressed constitutively [21] and, like the complement system, are evolutionarily ancient components. In comparison to antibiotics, AMPs may be considered "natural antibiotics" expressed across the phylogenetic kingdoms [22] and causing pathogen cell disruption through non-specific interactions with their membrane surface [23]. The majority of AMPs are cationic peptides that electrostatically interact with bacterial membranes or translocate into cells affecting intracellular targets.…”
Section: Renewing Antimicrobial Peptides Potentialmentioning
confidence: 99%
“…Amongst the challenges that hamper the in vivo efficacy of AMPs and delay their successful development for clinical use are (A) the potential loss of activity in the presence of low pH, saline, divalent cations, and serum or plasma proteins; (B) liability to degradation by tissue proteases; (C) potential hemolytic and/or cytotoxic effects; (D) potential immunogenicity and unclear pharmacokinetic properties; (E) low antimicrobial activity in clinically relevant environments, which is particularly important in the context of sepsis as a complication of MDR-associated wound infections; and (F) potential resistance to AMPs, although far less common than resistance to current antibiotics [ 133 , 134 ]. Several strategies have been developed to overcome the mentioned limitations and reduce the production costs of AMPs.…”
Section: Antimicrobial Alternatives Under Investigationmentioning
confidence: 99%